Control of solution MMA polymerization in a CSTR - Tanaka, Ken (University of Waterloo, 1997)
Simulation studies on the on-line control of polymerization reactors are numerous, and have been extensively employed. Proportional-integral-derivative (PID) controllers have been and continue to be in wide spread use throughout industry. This thesis work was to review the literature on the control of polymerization reactors, and to experimentally verify a novel PID controller tuning method on a well studied polymerization system. A continuous stirred tank reactor (CSTR) system for the solution homopolymerization of methyl methacrylate (MMA) in toluene was designed and built by a past Ph.D. student (Chien, 1992). He also developed a mechanistic model for the process. Several other students have studied system identification and control of this system. Recently, Wang, Barnes and Cluett (1995a) proposed a novel PID controller design method, which will be referred to as the W-C method from now on. The W-C method could be applied to a PID conversion controller on the CSTR and compared to Chien's results. PID control of conversion with differently tuned PID controllers as first simulated. Next, PID controllers tuned using the internal model control (IM) tuning method and the W-C method were applied in a long experimental run to verify the simulation results. The CSTR process had changed little in the five years since Chien's work. The IMC tuned controller was fast and able to control conversion at the desirable setpoints and recover from disturbances. The W-C tuned controller had a controller output signal as predicted by the simulations, and also controlled and recovered from disturbances well.
Keywords: Harvested from Collections Canada